Expedient Synthesis of Substituted Thieno[3,2-b]thiophenes and Selenopheno[3,2-b]selenophenes Through Cascade Cyclization of Alkynyl Diol Derivatives - Feng, Yingqi; Zhang, Xuelin; He, Ziqing; Zhao, Miaoshan; Chen, Lu; Li, Yibiao; Luo, Xiai (Molecules (Basel, Switzerland), 2024)
Thieno[3,2-b]thiophenes are used as key components in optoelectronic materials, porous hydrogen-storage hosts, organic solar cells, and polymer semiconductors. A step-efficient synthetic protocol was proposed herein for obtaining multisubstituted thieno[3,2-b]thiophene and selenopheno[3,2-b]selenophenes in moderate to good yields via the bisulfur/biselenium cyclization of alkynyl diols with I2/Na2S2O3 or selenium. Using this strategy, substitution patterns were obtained for backbone modification in functional materials.